Sensitive method for total selenium determination in garlic and nuts by UV–photochemical vapor generation coupled to atomic absorption spectrometry using mild conditions - Palatnik, Jaime (2023)
Photochemical vapor generation (PVG) coupled on–line to atomic absorption spectrometry using a flow injection mode was investigated for the determination of total Se in garlic and nut samples. In the presence of low molecular weight organic acid solutions, Se(IV) is converted by UV irradiation to volatile species which are transported to the heated quartz tube atomizer. Formic and acetic acids were tested as photochemical reagents and a mixture of 1.5 % (v/v) formic and 5% (v/v) acetic acid was the best alternative. Central composite design was employed for parameters optimization. The effect of potential interfering elements such as hydride–forming elements, transition metals and nitric acid was investigated to ascertain possible effects of the matrix on Se(IV) signal. Under optimized conditions a detection limit (LOD) of 33 ng g –1 (3S) was reached. Samples of garlic and nuts purchased at a local market were analyzed and Se concentrations spanned the range 0.36 to 248 µg g–1 . These results were compared with ICP–MS measurements utilizing an elliptical joint confidence region (EJCR) with bilinear least squares analysis, and good results were obtained.